Transarterial Chemoembolization Followed by Hepatic Arterial Infusion Chemotherapy Combined a Tyrosine Kinase Inhibitor for Treatment of Large Hepatocellular Carcinoma - Chen, Bin; Dai, Haitao; Yang, Jianyong; Zhang, Guiyuan; Wen, Chunyong; Xiang, Xianhong; Lin, Run; Huang, Yonghui (Current Cancer Drug Targets, 2023)
Objective: Evaluate the efficacy and safety of transarterial chemoembolization (TACE) sequential with hepatic arterial infusion chemotherapy (HAIC) and a tyrosine kinase inhibitor (TKI) for unresectable large hepatocellular carcinoma (HCC). Methods: Patients with HCC size > 70 mm were included. They received 1-3 cycles of TACE and sequential HAIC every 3-6 weeks for 2-6 cycles, with each cycle given over a period of 48 hours (oxaliplatin plus fluorouracil/leucovorin). Patients also received sorafenib or lenvatinib beginning at the first TACE cycle and continuing until disease progression. Objective response rate (ORR) at 3 months was the primary endpoint. Progression-free survival (PFS) and safety were the secondary endpoints. Results: From January 2020 to December 2020, 41 patients were included, who were divided into the drug-eluting bead TACE (DEB-TACE) group (n=13) and conventional TACE (cTACE) group (n=28). The overall ORR was 56.1% (23/41) using mRECIST criteria and 34.1% (14/41) using RECIST1.1 criteria. The median PFS of the cohort was 8 months. The ORR of the DEB-TACE group was 76.9% (10/13) vs. 46.4% (13/28) for the cTACE group (p = 0.06). The median PFS of the DEBTACE group was 12 months, and 6 months in the cTACE group (p = 0.09). Conversion hepatectomy was performed in 2 patients in the DEB-TACE group (15.4%), and in 3 patients in the cTACE group (10.7%). ALT/AST elevated, hypertension, nausea, and vomiting were the common treatment related adverse events. There was no treatment related death. Conclusion: TACE sequential with HAIC combined a TKI is a well-tolerated and promising tripletherapy for large, unresectable HCC.
Keywords: tyrosine kinase inhibitor